HOMI BHABHA’S MIMICRY AS REFLECTED IN TANIZAKI’S NAOMI - Setyowati, Yulis (Jurnal Sastra dan Budaya Dinamika, 2017)
This research focuses on mimicry based on the theory of Homi Bhabha in Tanizaki’s Naomi. The research is a qualitative research. The findings of the research shows that Naomi  indeed imitate, copy, and adapt the western culture. Naomi in imitating, copying and adapting western norm through their physical appearance  uses western products such as cosmetics, magazine, fabric, food and seeing movie and enjoying western music. Meanwhile, Naomi’s manners and behaviors confirm the applying of the notion of mimicry which is said as an imitating, copying and adapting the western culture. Naomi is described as good imitator of western culture not only in her physical appearance but also she performs some actions which mimic of western culture. Those actions are being punctual if she has an appointment, and  having a lot of male westerner friends. Keywords : mimicry, postcolonialism